2023
DOI: 10.3390/pathophysiology30010001
|View full text |Cite|
|
Sign up to set email alerts
|

LMP1-EBV Gene Deletion Mutations and HLA Genotypes of Nasopharyngeal Cancer Patients in Vietnam

Abstract: Nasopharyngeal carcinoma (NPC) is the most common cancer among head and neck cancers in Vietnam. We aimed to identify the rate of a 30 bp deletion mutation of the LMP1-EBV gene in nasopharyngeal biopsy tissue samples, the HLA genotypes of NPC patients, and the relationship between these two targets. Patients with NPC at Can Tho Oncology Hospital from September 2014 to December 2018 were selected. A length of 30 bp of the del-LMP1-EBV gene was analyzed using a PCR technique, and the HLA genotypes in patients’ b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Furthermore, we observed that endothelial cells expressing SELE, particularly those with the S149R mutation, significantly render stronger migration and tumorigenesis to malignant NPC cells. This supports the crucial role of E-selectin in interacting with cancer cells and modulating metastasis across various cancers 36,51–53 . Therefore, these findings suggest that the SELE- S149R may enhance the adhesion function of E-Selectin in endothelial cells, reshaping the key TME component to favor the progression of cancer cells 53 , consequently altering individual susceptibility to NPC.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, we observed that endothelial cells expressing SELE, particularly those with the S149R mutation, significantly render stronger migration and tumorigenesis to malignant NPC cells. This supports the crucial role of E-selectin in interacting with cancer cells and modulating metastasis across various cancers 36,51–53 . Therefore, these findings suggest that the SELE- S149R may enhance the adhesion function of E-Selectin in endothelial cells, reshaping the key TME component to favor the progression of cancer cells 53 , consequently altering individual susceptibility to NPC.…”
Section: Discussionsupporting
confidence: 71%
“…Stepwise conditional analysis localized three independently associated variants, including HLA-DQB1*03:01:01 , HLA-A: A_62_Q , and rs1050462 at HLA-B ( Tables 1, Table S1 ). Except for the two known associations at HLA-A: A_62_Q and HLA-DQB1*03:01:01 18,29 , the association of rs1050462 with NPC was a novel discovery whose signal is not attributed to previously reported HLA variants 8,10,11 (see Methods; P ≤ 3.23 × 10 -5 ; Table S3 ), according to an additional conditional analysis using an extended GD-SYSUCC cohort consisting of 1,583 cases and 3,049 controls with GWAS array data 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors would like to make the following corrections to the paper published [ 1 ] in Pathophysiology journal.…”
mentioning
confidence: 99%
“…Regrettably, following publication, concerns were brought to the attention of the publisher regarding a possible overlap between the article [ 1 ] and two earlier articles [ 2 , 3 ] originating from the same authorship group and published in another language.…”
mentioning
confidence: 99%